Expression of beta-keratin mRNAs and proline uptake in epidermal cells of growing scales and pad lamellae of gecko lizards - Alibardi, Lorenzo (Blackwell Science Inc, 2007)
Beta-keratins form a large part of the proteins contained in the hard beta layer of reptilian scales. The expression of genes encoding glycine–proline-rich beta-keratins in normal and regenerating epidermis of two species of gecko lizards has been studied by in situ hybridization. The probes localize mRNAs in differentiating oberhautchen and beta cells of growing scales and in modified scales, termed pad lamellae, on the digits of gecko lizards. In situ localization at the ultrastructural level shows clusters of gold particles in the cytoplasm among beta-keratin filaments of oberhautchen and beta cells. They are also present in the differentiating elongation or setae of oberhautchen cells present in pad lamellae. Setae allow geckos to adhere and climb vertical surfaces. Oberhautchen and beta cells also incorporate tritiated proline. The fine localization of the beta-keratin mRNAs and the uptake of proline confirms the biomolecular data that identified glycine–proline-rich beta-keratin in differentiating beta cells of gecko epidermis. The present study also shows the presence of differentiating and metabolically active cells in both inner and outer oberhautchen/beta cells at the base of the outer setae localized at the tip of pad lamellae. The addition of new beta and alpha cells to the corneous layer near the tip of the outer setae explains the anterior movement of the setae along the apical free-margin of pad lamellae. The rapid replacement of setae ensures the continuous usage of the gecko's adhesive devices, the pad lamellae, during most of their active life.